LAPORAN BARU: SPESIES LALAT BUAH TERPIKAT 4-(4-HIDROKSI-FENIL)-2-BUTANON = NEW REPORT: FRUIT FLY SPECIES RESPOND TO 4-(4-HIDROKSI-FENIL)-2-BUTANON - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Acetylation of 4-(4-hydroxy-penyl)-3-butene-2-one by anhydride of acetic acid catalyzed by sulphuric acid results in 4-(4-acetoxy-phenyl)-3-butene-2-one compound, and 4-(4-hydroxy-phenyl)-2-butanone compound as a by product. The first compound alone doesn t attract fruit flies, but a mixture of the two products attracts male fruit flies. This mixture was tested for its attractancy to thefruit flies in Bantul, Sleman and Kulon Progo regencies, Yogyakarta Special Province